Effects of Student Self-Determination Motivation on Student Academic Performance - Mukhoiyaroh Mukhoiyaroh; Yahya Aziz (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
The purpose of the study was to find the effect of Self-Determination Motivation and academic achievement of the students of the Faculty of Tarbiyah and Teaching Training UIN Sunan Ampel Surabaya and to reveal the motivation of self-determination in the lectures of the Faculty of Tarbiyah and Teaching Training UIN Sunan Ampel Surabaya. This study uses correlational quantitative methods with the research subjects of Tarbiyah students and Teachers at UIN Sunan Ampel. Sampling was done using a stratified random sampling technique from 676. The sample was taken randomly from 127 students from 8 study programs. Data was collected through self-determination motivation questionnaires and documentation of student academic scores, as well as with a statistical regression analysis technique using SPSS Version 23 simple linear and descriptive analysis. The t-count value is 7.721, with a significance value of 0.000. The t-table value obtained from the statistical table is 1.979. If a comparison is made, then t count > t table or the significance is < 5% significance level so that the self-determination motivation has a significant effect on academic ability at the significant level (5%). The results of the statistical analysis found intrinsic and extrinsic motivation and no amotivation was found in students of the Faculty of Tarbiyah and Teaching Training UIN Sunan Ampel Surabaya, and the variety of self-determination motivation was the intrinsic and extrinsic variety.